Power training in elite young soccer players: Effects of using loads above or below the optimum power zone - Loturco, I.; Pereira, L. A.; Reis, V. P.; Bishop, C.; Zanetti, V.; Alcaraz, P. E.; Freitas, T. T.; Mcguigan, M. R. (Journal of Sports Sciences, 2020)
This study aimed to examine the effects of two jump squat (JS) training programs involving different loading ranges in under-20 soccer players during a preseason period. Twenty-three elite young soccer players performed sprint speed (at 5-, 10-, and 20-m), change-of-direction (COD) speed, JS peak-power (PP), and countermovement jump (CMJ) tests pre and post four weeks of training. Athletes were pair-matched in two groups according to their optimum power loads (OPL) as follows: lower than OPL (LOPL; athletes who trained at a load 20% lower than the OPL) and higher than OPL (HOPL; athletes who trained at a load 20% higher than the OPL). Magnitude-based inferences were used to compare pre- and post-training measures. Meaningful increases in the PP JS were observed for both groups. Likely and possible improvements were observed in the 5- and 10-m sprint velocity in the LOPL group. Meanwhile, possible and likely improvements were observed in the CMJ, 5- and 10-m sprint velocity, and COD speed in the HOPL group. Overall, both training schemes induced positive changes in athletic performance. Soccer coaches and sport scientists can implement the JS OPL-based training schemes presented here, either separately or combined, to improve the physical performance of youth soccer players.